2016
DOI: 10.1016/j.eats.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Technique for Repair of Distal Biceps Tendon Avulsions With Intramedullary Cortical Button

Abstract: Patients who experience distal biceps tendon avulsions generally benefit from surgical intervention. Compared with nonoperative treatment, surgery has shown improved muscle endurance as well as increased flexion and supination strength. Although a number of surgical techniques exist, repair of the distal biceps through a single incision is gaining popularity. This may be due in part to patient preference and emerging technologies such as cortical button fixation, suture anchors, and intraosseous screws. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…Several surgical options have been described in literature: one incision-approach, using suture anchors, endobutton, biotenodesis screw for fixation, and a double-incision approach, using bone tunnels [8, 15, 19, 21, 22]. Standard and modified double incision approach differ one to each other in ulnar periosteum exposure, avoided by the Morrey’s muscle-splitting technique that reduces risk of synostosis [23, 24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several surgical options have been described in literature: one incision-approach, using suture anchors, endobutton, biotenodesis screw for fixation, and a double-incision approach, using bone tunnels [8, 15, 19, 21, 22]. Standard and modified double incision approach differ one to each other in ulnar periosteum exposure, avoided by the Morrey’s muscle-splitting technique that reduces risk of synostosis [23, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Others have also described a modified double-incision technique, introducing a muscle-splitting approach through the digits common extensor. More recently, with the advent of improved techniques and implants such as suture anchors, intraosseous screws and suspensory cortical buttons, single-incision techniques have once again gained popularity [14, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, more soft tissue dissection may place patients at risk for heterotopic ossification and subsequent proximal radioulnar synostosis. 8 Functionally limiting radioulnar synostosis rates as high as 7.0% were reported after dual-incision repairs. 20 In this study, no patients experienced radioulnar synostosis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other benefits of the single incision technique include improved cosmesis and avoidance of radioulnar synostosis. 8 Finally, several studies 11,12 showed that there are no major differences in tendon healing to cortical bone compared with healing to cancellous bone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation